The Influence of Obesity, Ovariectomy, and Greenshell Mussel Supplementation on Bone Mineral Density in Rats. (14th November 2021) - Siriarchavatana, Parkpoom; Kruger, Marlena C; Miller, Matthew R; Tian, Hong (Sabrina); Wolber, Frances M
ABSTRACT: Obesity is considered to impair long‐term health by disturbing multiple physiological functions. However, it remains a controversial issue as to whether obesity has beneficial or detrimental effects on bone health in postmenopausal women. The aims of this study were to investigate the relationships between obesity and bone mineral density (BMD) under conditions of ovarian hormone deficiency in an animal model and to evaluate the potential health benefits of Greenshell mussel (GSM) on bone health. A total of 144 adult female Sprague–Dawley rats were fed from age 12 weeks on one of four diets (normal [ND]; ND + GSM; high fat/high sugar [HF/HS]; HF/HS + GSM; n = 36 per diet). At age 20 weeks, after a dual‐energy X‐ray absorptiometry (DXA) scan, 12 of the rats on each diet underwent ovariectomy (OVX) and the remaining rats were left intact. Twelve of the intact rats in each diet group were culled at age 26 weeks (short‐term cohort). The remaining rats were culled at age 48 weeks (long‐term cohort). Rats were DXA scanned before cull, then various fat pads were dissected. The results revealed that HF/HS rats and OVX rats dramatically increased body weight and fat deposition in correlation with leptin. In the long‐term cohort, vertebral spine BMD rapidly declined after OVX. At termination, the OVX rats had decreased plasma bone turnover markers of CTX‐1 and TRAP when compared with sham rats. Significantly higher BMD was found in OVX rats fed the HF/HS diet compared with ND, but this difference was not recapitulated in intact rats. BMD of right femur was significantly increased 5% to 10% by GSM in the short‐term cohort. The data demonstrated that obesity can be beneficial by increasing BMD in OVX rats, and this may extrapolate to postmenopausal women as adipocyte‐produced estrogen may slightly compensate for the reduction in ovarian hormones. Finally, the data showed that GSM may be beneficial to bone health by increasing BMD accrual. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.